PERAN PENTING FILSAFAT ILMU BAGI PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM - Didit Haryadi; Kerwanto; Arifin Ilham; Zaenal Mutakin (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
The close relationship between philosophy and education significantly influences the formation of individual thinking and character. In the context of Islamic education, integrating philosophical knowledge plays a crucial role in developing students' critical, logical, and ethical thinking. This study aims to explore the application of philosophy within the Islamic education system and its benefits for students' intellectual and spiritual growth. Using a qualitative approach through literature review, this research explains the main concepts of philosophy and their correlation with the values of Islamic education. The findings indicate that incorporating philosophy into the Islamic education system can contribute to enhancing critical, logical, and analytical thinking skills, as well as deepening the understanding of ethics and morals in Islam. Moreover, the study of philosophy can enrich spiritual insights and help students comprehend the complexities of life more profoundly. The research concludes that implementing philosophy in Islamic education is a vital step in shaping individuals who are intellectually and spiritually astute, with strong moral integrity.